Treatment Non-Adherence Among Patients With Poorly Controlled Type 2 Diabetes Am¬bulatory Care Settings In Southwestern Nigeria (2014)
Background: Poor adherence to prescribed therapy among patients with chronic diseases is a growing concern which un¬dermines the benefits of current medical care. Objectives: To evaluate the pattern of treatment non-adherence among ambulatory patients with poorly controlled type 2 diabetes in southwestern Nigeria, and to determine the possible factor(s) that accounted for such non-adherence with a view to identifying areas of future intervention to improve outcome. Methods: A prospective cross-sectional interview using the concept of RIM (Recognize, Identify and Manage) model was used to evaluate adherence to treatment recommendations among 176 consented patients recruited from the endocrinology out-patient clinics of two teaching hospitals in southwestern Nigeria between November, 2010 and January, 2011. Results: Overlaps of non-adherence behavior were obtained. More than three-quarter (153; 88.4%) were not aware of in¬dication for each of the prescribed medications, 26 (15.3%) correctly described regimen as prescribed. The factorsidentified as possible barriers to medication adherence include practical (145; 40.1%), knowledge (103; 28.5%), and attitudinal (114; 31.5%) barriers. Dietary non-adherence was mostly due to inappropriate guidance (62; 33.7%). Conclusions. The arrays of non-adherence behavior among the cohort further emphasize the need for patient-centered approach as a reasonable strategy in resolving non-adherence problems in routine clinical practice.